Qualitative Analysis at Scale : An Application to Aspirations in Cox's Bazaar, Bangladesh - Ashwin, ,Julian; Rao, Vijayendra; Biradavolu, Monica; Haque, Arshia; Khan, Afsana; Krishnan, Nandini; Peer, Nagy (World Bank, Washington, DC, 2022)
Qualitative work has found limited use in economics largely because it is difficult to analyze at scale due to the careful reading of text and human coding it requires. This paper presents a framework with which to extend a small set of hand-coding to a much larger set of documents using natural language processing and thus to analyze qualitative data at scale. The paper shows how to assess the robustness and reliability of this approach and demonstrates that it can allow the identification of meaningful patterns in the data that the original hand-coded sample is too small to identify. The approach is applied to data collected among Rohingya refugees and their Bangladeshi hosts in Cox’s Bazaar, Bangladesh, to build on work in anthropology and philosophy that distinguishes between ambition–specific goals, aspiration–transforming values, and navigational capacity, which is the ability to achieve ambitions and aspirations. The findings demonstrate that these distinctions can have important policy implications.